EAACI Food Allergy and Anaphylaxis Guidelines. Protecting consumers with food allergies: understanding food consumption, meeting regulations and identifying unmet needs. - Muraro, A.; Hoffmann-Sommergruber, K.; Holzhauser, T; Poulsen, L. K.; Gowland, M H; Akdis, C. A.; Mills, EN C; Papadopoulos, N; Roberts, G.; Schnadt, S; van Ree, R.; Sheikh, A; et al. (Allergy, 2014)
Individuals suffering from IgE-mediated food allergy usually have to practise life-long food allergen avoidance. This document aims to provide an overview of recent evidence-based recommendations for allergen risk assessment and management in the food industry and discusses unmet needs and expectations of the food allergic consumer in that context. There is a general duty of care on the food industry and obligations in European Union legislation to reduce and manage the presence of allergens alongside other food hazards. Current evidence enables quantification of allergen reference doses used to set-up reliable food safety management plans for some foods. However, further work is required to include a wider variety of foods and to understand the impact of the food matrix as well as additional factors which affect the progression and severity of symptoms as a function of dose. Major concerns have been raised by patients, carers and patient groups about the use of precautionary 'may contain' labelling to address the issue of unintended presence of allergens; these therefore need to be reconsidered. New and improved allergen detection methods should be evaluated for their application in food production. There is an urgent requirement for effective communication between healthcare professionals, patient organizations, food industry representatives and regulators to develop a better approach to protecting consumers with food allergies.